Molecular Dynamics Studies of The Effects of Copper on The Mechanical Properties of Aluminum - Rudianto, Haris; Haryadi, Deni (Master Program in Mechanical Engineering, Gunadarma University, 2024)
In this research, molecular dynamics (MD) simulations were performed to model the effects of copper content on aluminum properties. Copper has a low solubility in aluminum. Therefore, the main purpose of this research is to study the influence of copper content (Cu) on the mechanical properties of aluminum. Modeling and simulation of nano indentation and uniaxial tension tests were carried out to observe the mechanical properties under the conditions of copper content starting from 0.5 up to 10wt% at 300oK. The interactions between the atoms of aluminum and copper were modeled using Embedded Atom Method (EAM) potentials. The calculation showed that a higher amount of copper increased the tensile strength of aluminum, and in this research,10wt% copper gave the highest tensile strength. But when it comes to the nano indentation test to determine hardness value, it showed that 1wt% copper gave the highest hardness, it assumes that this is related to localization of nano indentation test position optimum formation of intermetallic aluminum-copper, Al2Cu on a certain area.